Biomarkers in Inflammatory Myopathies—An Expanded Definition - Benveniste, Olivier; Goebel, Hans-Hilmar; Stenzel, Werner (Frontiers in Neurology, 2019)
Biomarkers as parameters of pathophysiological conditions can be of outmost relevance for inflammatory myopathies. They are particularly warranted to inform about diagnostic, prognostic and therapeutic questions. As biomarkers become more and more relevant in daily routine, this review focusses on relevant aspects particularly addressing myopathological features. However, the level of evidence to use them in daily routine at presence is low, still since none of them has been validated in large cohorts of patients and rarely in independent biopsy series. Hence, they should be read as mere expert opinions. The evaluation of biomarkers as well as key biological parameters is an ongoing process, and we start learning about relevance of them, as we must recognize that pathophysiology of myositis is biologically incompletely understood. As such this approach should be considered an essay towards expansion of the definition ‘biomarker’ to myositis, an emerging field of interest in biomedical research.